Mechanosensory neurons control sweet sensing in Drosophila - Yong Taek Jeong (Nature Portfolio, 2016)
How different sensory modalities interact to control feeding is poorly understood. Here, authors show that in Drosophila, activation of labellar mechanosensory neurons causes inhibition of sweet-sensing gustatory receptor neurons, as a result, Drosophilaprefer soft food at the expense of sweetness.